ANALISIS KADAR HEMOGLOBIN WHOLE BLOOD BERDASARKAN DURASI PENYIMPANAN DI UTD RSUD BAHTERAMAS - Widuri, Sasi; Lentera Afrida Kusumawardani; Kwarta, Cityta Putri; Amalia, Yustisia; Samsulhadi, Wiwid (Rena Cipta Mandiri, 2026)
Maintenance of hemoglobin (Hb) levels in Whole Blood (WB) is crucial to ensure the quality and efficacy of transfusions, as the storage process can induce biochemical changes. Preliminary observations at RSUD Bahteramas indicated fluctuations in Hb levels during the early storage period. This study aimed to analyze the differences in Hb levels between the 5th and 10th day of WB storage at the Blood Transfusion Unit of RSUD Bahteramas. An analytical study with a cross-sectional approach was conducted on 10 WB samples selected using simple random sampling. Hb levels were measured using the LANDWIND Hematology Analyzer, and data were analyzed descriptively and with an independent t-test. Results showed that on day 5, only 50% of samples met quality specifications, whereas by day 10, compliance increased to 90%. A significant difference in Hb levels was observed between the two storage periods (p<0.05). It is concluded that optimal cold chain management can maintain Hb stability up to the 10th day of storage.